Interpassive Gambling: The Case of Slot Machine Vlogs on YouTube - Hoebanx, Pauline; French, Martin (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2023)
Slot machines are recognized as a particularly risky form of gambling. However, there is a form of slot machine consumption that seems to have largely escaped the notice of regulators and scholars: the streaming of slot machine play on YouTube and other platforms. In this article, we present the results of our qualitative study of 21 slot machine videos. Our study examines how these videos portray gambling and how they align with the norms of YouTube’s platform economy. Our analysis underscores the representation of slot machine gambling in this under-regulated media, emphasizing different tactics of viewer manipulation. We introduce the concept of interpassive gambling to reflect the ways that user-generated videos are a form of diffusion of gambling mechanics beyond traditional gambling venues. We conclude by calling for more scholarly and regulatory attention to this gamblified site of media consumption.